2020
DOI: 10.1002/cam4.3094
|View full text |Cite
|
Sign up to set email alerts
|

Reverse swing‐M, phase 1 study of repurposing mebendazole in recurrent high‐grade glioma

Abstract: BackgroundRelapsed high‐grade glioma has dismal outcomes. Mebendazole has shown promising activity against glioma in in‐vitro and in‐vivo studies. Hence, we undertook a phase 1 study to repurpose mebendazole in the treatment of glioblastoma.MethodsWe conducted a phase 1 study (accelerated titrated design 4) of mebendazole in patients with recurrent glioblastoma (GBM). Patients eligible for re‐irradiation were enrolled in arm A1 (radiation with concurrent temozolomide 75 mg/m2 daily during the course of radiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…We demonstrated that MBZ exerted more potent anti-proliferation activity than cisplatin in human HNSCC cells, and effectively inhibited cell proliferation, cell cycle progression and cell migration, and induced apoptosis in HNSCC cells [ 18 ]. Other studies indicate that MBZ and its derivatives exerted potent anticancer effect in non-small cell lung cancer [ 19 , 20 ], adrenocortical carcinoma [ 22 ], medulloblastoma [ 28 ], melanoma [ 21 ], leukemia and myeloma [ 24 ], glioblastoma multiform [ 23 , 34 ], colon cancer [ 26 ], cholangiocarcinoma [ 27 ], breast cancer [ 25 , 29 ], gastric cancer [ 30 ], mouse hepatoma [ 31 ], and thyroid cancer [ 32 ]. In this study, our results are the first to demonstrate that MBZ can overcome cisplatin resistance and synergize with cisplatin in inhibiting cell proliferation and inducing apoptosis in cisplatin-resistant ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that MBZ exerted more potent anti-proliferation activity than cisplatin in human HNSCC cells, and effectively inhibited cell proliferation, cell cycle progression and cell migration, and induced apoptosis in HNSCC cells [ 18 ]. Other studies indicate that MBZ and its derivatives exerted potent anticancer effect in non-small cell lung cancer [ 19 , 20 ], adrenocortical carcinoma [ 22 ], medulloblastoma [ 28 ], melanoma [ 21 ], leukemia and myeloma [ 24 ], glioblastoma multiform [ 23 , 34 ], colon cancer [ 26 ], cholangiocarcinoma [ 27 ], breast cancer [ 25 , 29 ], gastric cancer [ 30 ], mouse hepatoma [ 31 ], and thyroid cancer [ 32 ]. In this study, our results are the first to demonstrate that MBZ can overcome cisplatin resistance and synergize with cisplatin in inhibiting cell proliferation and inducing apoptosis in cisplatin-resistant ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Its anticancer properties were notably demonstrated in gliomas [11,14,34], and there are currently three ongoing clinical trials in high‐grade gliomas in both adult and pediatric patients (NCT01729260, NCT02644291, and NCT01837862). Furthermore, a recent phase I trial demonstrated that administration of MBZ concomitantly with radiotherapy and temozolomide chemotherapy was safe in high‐grade glioma patients [35].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, this would be a suitable approach to achieve an improved treatment for the elderly who cannot tolerate higher doses. [ 38 , 39 ]. The prognosis for elderly, unfit patients is still bleak with current treatments.…”
Section: Discussionmentioning
confidence: 99%